HERBERT M. McLUHAN: METHODOLOGY OF THE INTERRELATION OF CULTURE, MEDIA, AND COMMUNICATIONS - Onopriyenko, Valentyn (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Itroduction. McLuhan created a conceptual model of the historical dynamics of society, in the center of which there is the problem of the type and method of communication. The aim and tasks are the studies of the basic ideas of the historical dynamics of the society in the concept of M. McLuhan. Research methods are based on the methodological aspects of the concept of the historical dynamics of society according to M. McLuhan. Research results. The heyday of the popularity of McLuhan and his work came in the 1960s-1970s, with the development of the Internet, his theories acquired a new meaning and at the turn of the XX-XXI centuries again found themselves at the center of theoretical discussions. A certain type of communication (communication technology) not only defines, but creates a social world – a "galaxy", which has its area and, despite the possibility of expanding or changing configurations, superimposing galaxies on top of each other or mutually passing through, nevertheless has fixed borders. McLuhan understands communication as the exteriorization of a person's sensory ability to perceive, highlighting, based on this criterion, audio (or speech) communication and video (or visual) communication, which, in turn, forms the basis for the differentiation of audio and video cultures, that is, "cultures of hearing" and "cultures of sight". Discussion. Historically, the first is the era of the "tribal man", that is, the era of oral speech (audio culture), in connection with which the "sensory balance of the tribal man" is characterized by syncretism and inclusion in the mutually resonant speech of the members of the community, which corresponds to the mythological syncretism of consciousness and the dissolution of the individual in the tribal team. In addition, the "culture of hearing" generates a style of thinking that expressly demonstrates the paternalistic attitudes of the mass consciousness. The changes brought about by the introduction of writing and printing are as follows: a cold, monotonous visual world instead of an emotional, varied oral world; loss of the mystical element; one feature - rationality of thinking - instead of all the richness of feelings. Conclusion. The printed word, which made writing the basis of mass communications, granted the individual such rights as the selection of information (while one cannot escape from the sounding voice, one can read and watch anything), its free interpretation (one’s point of view as opposed to obedience), criticism and the ability to do with this information in his own way - in fact, the right to individuality.